The Effect of Gender Diversity, Profitability and Firm Size on Stock Price of Jakarta Islamic Index Companies with Capital Structure as Moderating Variable - Hutabarat, Francis; Majilang, Deanna Beryl (UPT Publikasi Ilmiah UNISBA, 2025)
In this study, we wanted to see if the way a company's money is arranged affects how different things like gender diversity, how much money it makes, how big it is, and its stock price relate to each other. We looked at 30 companies listed on the Jakarta Islamic Index in Indonesia. We used information from things like reports and websites. Specifically, we focused on annual reports from 2019 to 2022. We studied a total of 120 companies. To analyze the data, we used a few different methods with a software called Eviews. What we found was that gender diversity, how much money a company makes, and how big it is, all influence its stock price. Interestingly, the way a company's money is arranged didn't change how gender diversity or size affected stock price, but it did affect how profitability influenced it. This suggests that focusing on making profits could be key for companies listed on the Islamic Index to improve their stock prices. Our findings could help managers of these companies make decisions about how to manage their finances and boost profits. They could also be useful for shaping policies for Islamic Index companies in Indonesia